HUKUM MENYEWAKAN RAHIM MENURUT MAJELIS ULAMA INDONESIA (MUI) KALIMANTAN BARAT: - - Yeyen Raja Syah Harahap; Abu Bakar; Nur Hakimah (Al-Aqad, 2023)
The purpose of this research is to find out the implementation of uterine leasing, the opinion of the Indonesian Ulema Council (MUI) of West Kalimantan, and the concept of the legal basis underlying the views of the Indonesian Ulema Council (MUI) of West Kalimantan on uterine leasing. The type of research conducted to obtain the data desired by researchers using empirical field research. The research technique uses a descriptive qualitative approach. The sources used by researchers use primary data and secondary data. The techniques used to collect data are interview techniques, and documentation. Based on the research conducted by researchers, it can be concluded that; 1) The practice of renting a uterus is an activity that brings harm to the child from renting a uterus and the surrogate mother, 2) MUI West Kalimantan argues that the practice of renting a uterus is tantamount to degrading the dignity of women because it is considered the same as selling women's honor, and MUI West Kalimantan argues that renting a uterus includes adultery. 3) The basic concept and legal basis used to strengthen the opinion of MUI West Kalimantan on the issue of the practice of renting a uterus is based on Islamic law sources, namely the Qur'an, Hadith, and the consensus of the scholars.